Optimizing risk factors influence Intensive Care stay after Hyperthermic Intraperitoneal Chemotherapy? An observational cohort study - Hamed Elgendy (11570543) (2022)
Background It may be necessary to admit patients receiving Hyperthermic Intraperitoneal Chemotherapy (HIPEC) to the intensive care unit (ICU). They were required to evaluate the length of ICU stay (LOS) following HIPEC, as well as their survival rates and risk factors that influence LOS. Methods 74 HIPEC patients were observed after being admitted to the ICU. Their assignments were made based on their LOS at the ICU. Short stay group, patients who stayed in the ICU for three days or less (S-group) and patients who stayed for three days or longer (L-group). Results Survival rates for both groups were comparable. After HIPEC, they exhibited intraoperative hypotension (P = 0.015), hyopthermia (P = 0.014), and hyperglycemia (P = 0.010). Additionally, patients in group L underwent longer surgeries (P = 0.013), lost more blood (P = 0.043), and required more transfusions (P = 0.001). Subjects in group-L had higher SOFA, fentanyl, and vasopressor requirements (all P 0.001), higher ALT and AST levels, disrupted K, lower Na, and higher INR levels (all P 0.001), as well as a higher APACHE II score (P = 0.007). Preoperative BUN had an independent risk factor for LOS of 0.861; (95% CI), (0.742- 0.999); P = 0.048; and crystalloid transfusion had an independent risk factor of 1.000; (95% CI), (0.999- 1.000); P = 0.003. Conclusions Transfusions of crystalloids and BUN were independent risk factors for extended LOS. ICU LOS had no impact on survival. All measures should be taken to control hemostasis in vulnerable HIPEC participants. Other Information Published in: Cancer Treatment and Research Communications License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ctarc.2022.100653